(untitled) (Journal of the College of Basic Education, 2022)
This paper sheds light on the issue of corruption in Nigeria among the political classes. By a modern novel, under the title A Man of the People written by a well-known Nigerian writer called Chenuia Achebe. He lampoons the political period of the first republic of Nigeria’s existence after its independence. He reveals that corruption and governmental influence was seen as two sides of a coin. Leaders come to power purely for the intentions of falling up their own pockets to support their followers and clans, at the expense of the people living in poverty. The Minister of culture utilizes his role and influence to increase his personal fortune rather than to develop the culture of the country. A Man of the People is a gripping novel, which vividly describes the main characters who are the bootlicking Odili and the corrupting minister Chief Nanga. This novel chronicles the politics of African country, and its eat-and-let-eat leaders. The novel also depicts how one can reach the peak of the power by dirty ways such as deception, tribalism, bribery and nepotism.